Anatomia óssea, muscular e do movimento do membro pelvino do lobo-guará Chrysocyon brachyurus (Carnivora: Canidae) - Ribeiro, Priscilla Rosa Queiroz (2018)
In order to collaborate in the elaboration of policies for the conservation of species, especially those threatened with extinction, such as Chrysocyon brachyurus, conducting diverse researches with such species is fundamental. Although C. brachyurus is among the most represented species in the publications (about 30), along with the Panthera onca (jaguar, Puma concolor (puma), Cerdocyon thous (lobinho) and Leopardus pardalis (jaguatirica); of information about ecology and population dynamics of the species, among others. The lack of information on the morphology of this animal can be added to the others. The aim of the present thesis was to describe the anatomic bone and muscle characteristics of the pelvic limb of C. brachyurus and to analyze the light of osteometry and movement anatomy. The three specimens of Chrysocyon brachyurus (Illiger, 1815) were used, two male specimens s and a female, belonging to the Laboratory of Teaching and Research in Wild Animals (LAPAS) of the Faculty of Veterinary Medicine of the Federal University of Uberlândia - UFU, in the city of Uberlândia. Initially, the specimens were fixed in aqueous solution of 10% commercial formaldehyde and stored in a solution of equal concentration. Subsequently, they were prepared using the usual macroscopic anatomical techniques. The cadavers were sectioned transversely to the lumbar region of the vertebral column, between the L2 and L3 vertebrae, the skin, adipose tissue and muscle fascias of the pelvic limbs were removed and the muscles of this region were dissected. The preparation of the bones occurred through the process of maceration in boiling water. The bones and muscles of the pelvic limb of C. brachyurus were described, divided into the pelvic limb, thigh, leg and foot. Bone measurements were presented and the osteometric indexes were calculated. Bone fixation points were demonstrated and inferences were made on the movements of the pelvic limbs of the animals. Although C. brachyurus commonly does not move at high speeds, the osteological, osteometric and myological characteristics of the pelvic limb of this species suggest the ability of this animal to reach high speeds.